Emotions detection on an ambient intelligent system using wearable devices - Costa, Angelo (2016)
In this paper we present an Ambient Intelligent System, the iGenda, and the integration of a wearable device. The aim is to detect emotional states through the wearable device and ultimately represent and manage the social emotion of a group of entities. The advantage of this action is that its usability is in line with retirement homes and similar places, where the community is extended and an harmonious environment is imperative. The iGenda serves has the visual interface and the information centre, receiving the information from the wearable device and managing the community emotion by sending information to the care-receivers, caregivers, or changing home parameters (like music or lighting) to achieve an specific emotion (such as calm or excitement). Thus the goal is to provide an affective system that directly interacts with humans by discreetly improving their lifestyle.